Development of SX chart for quality control - Ng, Charmaine Xue Ming. (2012)
This project develops the algorithm and presents the methodology for designing the optimal xbar , SX, and CUSUM charts. The optimal design parameters are obtained by minimizing the loss function. The out-of-control detection effectiveness, as well as